The Role of Financial Performance in Mediating the Relationship Between Green Innovation and Eco-Efficiency on Company Value - Amalo, Fitriningsih; Husen, Gayatri Nahdiyah (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Environmental pollution resulting from increasingly advanced industrial development has become one of the basic assessments for investors in making investment decisions. Environmental pollution that occurs can be prevented by implementing green innovation and eco-efficiency strategies so that companies are able to innovate in an environmentally friendly manner and minimize costs incurred for production. A company is expected to have good financial performance so that it can increase company value and convince investors in making decisions. This research is quantitative research with a research sample of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2022 period using purposive sampling research techniques. The research results show that the application of green innovation has an effect on company value, while eco-efficiency and financial performance have no effect on company value. Financial performance is unable to mediate the relationship between green innovation and eco-efficiency on company value.